Potential harms of supplementation with high doses of antioxidants in athletes - Li, S.; Fasipe, B.; Laher, I. (Journal of Exercise Science & Fitness, 2022)
Vigorous exercise generates large amounts of reactive oxygen species (ROS) as a result of the consumption of large volumes of O2 in athletes, causing some athletes to consume antioxidants in the erroneous belief that this will counteract the damaging effects of ROS. There is currently no convincing evidence to support the benefits of antioxidant supplementation in acute physical exercise and exercise training. On the contrary, exogenous antioxidants prevent some physiological functions of free radicals that are needed for cell signaling, causing higher dosages of antioxidants to hamper or prevent performance-enhancing and health-promoting training adaptation such as mitochondrial biogenesis, skeletal and cardiac muscle hypertrophy, and improved insulin sensitivity. However, there remains the perception that antioxidants can counterbalance oxidative stress and benefit exercise adaptation and performance in athletes. It is likely that the negative effects of high doses of antioxidant supplementation exceed their potential benefits. We discuss some proposed pathways of potential side effects of exogenous antioxidant supplementation in athletes.